Musculoskeletal and Gait Characteristics in Patients with Stickler Syndrome: A Cross-Sectional Study - Juan José Fernández-Pérez; Paloma Mascaraque-Ruiz; Carlos Martín-Gómez; Ignacio Martínez-Caballero; Teresa Otón; Loreto Carmona; Sergio Lerma-Lara (MDPI AG, 2022)
Background: Stickler syndrome (SS) is a connective tissue disorder of fibrillary collagen with very variable clinical manifestations, including premature osteoarthritis and osteopenia. This musculoskeletal alteration may affect gait maturity or produce strength difficulties. Objective: Our aim was to describe the musculoskeletal characteristics, bone stiffness, gait kinematics, and kinetics of SS patients. Methods: This is a cross-sectional study of children and youngsters with SS recruited by telephone calls through the Spanish SS Association. All participants underwent an analysis of musculoskeletal characteristics, including a 3D gait analysis. Results: The sample included 26 SS patients, mainly boys (65.4%) with a median age of 11 (IQR 5-14). The manual muscle testing was normal in 88.5% of patients. The median distance covered in the 6-min walking test was 560.1 ± 113.4 m. Bone stiffness index scores were 70.9 ± 19.7 for children under 10 years and 88.3 ± 17.5 for children older than 10 years. The gait indicators GPS and GDI were: 7.4 ± 1.9 and 95.3 ± 9.7, respectively, for the left side and 6.8 ± 2.0 and 97.7 ± 9.5 for the right side, respectively. Conclusions: In our series of patients with SS, we found muscle-articular involvement does not have a high impact on strength or gait problems. More work is needed to understand the effect of SS on the musculoskeletal system.